Pelatihan Peningkatan ICT Dalam Pelaksanaan AKM Siswa SDN 1 Bojong Cilimus - Erik Kurniadi; Endra suseno; Ragel Trisudarmo (JUPNA: Jurnal Pengabdian Astina, 2023)
The National Assessment is an evaluation program organized by the Ministry of Education and Culture to improve the quality of education by photographing the inputs, processes and outputs of learning in all educational units. Minimum Competency Assessment (AKM) is conducted to measure reading literacy and numeracy. Reading literacy is defined as the ability to understand, use, evaluate, reflect on various types of written texts to develop individual capacities as citizens of Indonesia and citizens of the world and to be able to contribute productively to society. Numeracy is the ability to think using mathematical concepts, procedures, facts, and tools to solve everyday problems in various types of contexts that are relevant to individuals as citizens of Indonesia and the world. Prior to the implementation of AKM at SDN 1 Bojong Cilimus, it was necessary to carry out a simulation for grade 5 students so that the implementation of AKM could run smoothly and students could work on literacy and numeracy questions properly according to the expectations of all parties. Keywords: national assessment, minimum competency assessment, literacy, numeracy, students